Early menarche is associated with increased risk of asthma: Prospective population-based study of twins. Issue 5 (May 2015) - Lieberoth, Sofie; Gade, Elisabeth; Kyvik, Kirsten Ohm; Backer, Vibeke; Thomsen, Simon Francis
Summary Aim To examine the association between early menarche and risk of post-menarcheal asthma. Methods Using data from two multidisciplinary questionnaire surveys, conducted eight years apart, we prospectively studied 10, 648 female twins, 12–41 years of age, from the nationwide Danish Twin Registry. Early menarche was defined as menarche before 12 years of age. We performed a cohort analysis and a co-twin control analysis including twin pairs discordant for incident asthma. Results Early menarche was observed in 9.3% of the individuals. The eight-year cumulative incidence of asthma was higher in girls with early menarche compared to girls without early menarche (7.4 vs. 4.5%), OR = 1.71 (1.31–2.22), p < 0.001; also after adjustment for BMI, current age, physical activity, education, and smoking, OR = 1.53 (1.15–2.04), p = 0.003. The unadjusted risk of asthma was increased by 8% (1–15%), p = 0.041 per year earlier menarche occurred. Among 167 twin pairs discordant for incident asthma, there was a non-significant tendency towards early menarche being more common in the asthmatic than the non-asthmatic co-twin (12.0 vs. 9.6%), OR = 1.57 (0.61–4.05), p = 0.350. The risk of asthma was not uniform in discordant monozygotic and dizygotic twins. Conclusion Early menarche is associated with increased risk of asthma among Danish female twins independently of BMI, age, physical activity, educational level and smoking. Results indicate a complex relationship possibly mediated through innate and non-genetic effects.